Evaluation of Fintech Use Using Methods Technology Acceptance Model (TAM) - Demianus Softer Jefdy Bawala; Andeka Rocky Tanaamah (Jurnal Indonesia Sosial Teknologi, 2024)
The rapid increase in the use of technology, especially finance (fintech) in recent years has changed the way we conduct financial transactions with digital payment systems. However, the acceptance and adoption of this technology are still a concern for researchers and practitioners in this field. This study aims to evaluate the use of fintech in the context of digital payments by applying the Technology Acceptance Model (TAM) method version 2 where the TAM model will be used to measure and analyze the factors that influence user acceptance of the use of fintech in digital payments. Through this research, it is hoped that a better understanding can be obtained of the factors that influence user acceptance of fintech in digital payments, especially for the benefit of further development. The approach used in this research is quantitative by using a questionnaire as a data collection tool. Respondents for this study were selected from groups of users of digital payment applications such as OVO and Gopay.